2022
DOI: 10.1038/s41591-022-01908-x
|View full text |Cite
|
Sign up to set email alerts
|

Programmable antivirals targeting critical conserved viral RNA secondary structures from influenza A virus and SARS-CoV-2

Abstract: Influenza A virus's (IAV's) frequent genetic changes challenge vaccine strategies and engender resistance to current drugs. We sought to identify conserved and essential RNA secondary structures within IAV's genome that are predicted to have greater constraints on mutation in response to therapeutic targeting. We identified and genetically validated an RNA structure (packaging stem-loop 2 (PSL2)) that mediates in vitro packaging and in vivo disease and is conserved across all known IAV isolates. A PSL2-targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Multiple studies suggest that biologically functional RNA motifs exist in regions of strong primary sequence conservation and that suppression of synonymous codon usage may be a result of maintaining RNA structure [ 82 84 ]. Additionally, the introduction of synonymous mutations within conserved regions of vRNA packaging signals has been shown to dramatically reduce genome assembly [ 83 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies suggest that biologically functional RNA motifs exist in regions of strong primary sequence conservation and that suppression of synonymous codon usage may be a result of maintaining RNA structure [ 82 84 ]. Additionally, the introduction of synonymous mutations within conserved regions of vRNA packaging signals has been shown to dramatically reduce genome assembly [ 83 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Is frequent re-boosting a viable vaccine option, e.g., via self-administered home nasal vaccines? Also to be considered are possible ancillary roles for prophylactic antivirals, including “programmable antivirals” targeting conserved structures, 142 antibodies, including therapeutic IgA 143 and innate immunity stimulators as adjuncts to imperfect vaccines. It remains to be seen if vaccination and prophylaxis can be effectively combined at the population level.…”
Section: Vaccine-related Questions Of Route Of Administration Antigen...mentioning
confidence: 99%
“…Two ASOs, LNA-12.8 and LNA-14.3, targeting the RNA motif of N and 5′UTR/ORF1ab, respectively, significantly reduced the viral titer of SARS-CoV-2. The experiments conducted on Syrian hamsters showed that LNA-12.8 prevents or mitigates SARS-CoV-2 transmission, diminishing virus titer in the lungs [ 87 ].…”
Section: Sars-cov-2mentioning
confidence: 99%
“…The influenza virus mutates rapidly and can develop resistance to antiviral drugs. The group of Hagey et al characterized the loop-stalk structure of PSL2 RNA, which serves as a packaging signal for the PB2 segment [ 87 ]. First, the secondary RNA structure in PB2 that mediates the packaging was mapped.…”
Section: Influenza a Virusmentioning
confidence: 99%
See 1 more Smart Citation